2015
DOI: 10.1038/srep12237
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Polarization Switching in Polycrystalline BiFeO3 Films by 2D Piezoresponse Force Microscopy

Abstract: For rhombohedral multiferroelectrics, non-180° ferroelectric domain switching may induce ferroelastic and/or (anti-)ferromagnetic effect. So the determination and control of ferroelectric domain switching angles is crucial for nonvolatile information storage and exchange-coupled magnetoelectric devices. We try to study the intrinsic characters of polarization switching in BiFeO3 by introducing a special data processing method to determine the switching angle from 2D PFM (Piezoresponse Force Microscopy) images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 49 publications
1
17
0
1
Order By: Relevance
“…It was reported, that under electrical poling, polarization reorientation induces a spin flop in BFO . Direct changes in the nature of the antiferromagnetic domain structure in BFO thin films was observed by application of an external electric field by combining piezoresponse force microscopy imaging of ferroelectric domains and x‐ray photoemission electron microscopy imaging of antiferromagnetic domains . This research showed that the ferroelastic switching events (i.e., 71° and 109°) leads to a corresponding rotation of the magnetization plane in BFO thin films and has paved the way for further study of this material with intent of a control of ferromagnetism at room temperatures.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…It was reported, that under electrical poling, polarization reorientation induces a spin flop in BFO . Direct changes in the nature of the antiferromagnetic domain structure in BFO thin films was observed by application of an external electric field by combining piezoresponse force microscopy imaging of ferroelectric domains and x‐ray photoemission electron microscopy imaging of antiferromagnetic domains . This research showed that the ferroelastic switching events (i.e., 71° and 109°) leads to a corresponding rotation of the magnetization plane in BFO thin films and has paved the way for further study of this material with intent of a control of ferromagnetism at room temperatures.…”
Section: Introductionmentioning
confidence: 83%
“…In several experimental studies it is shown that the magnetic sublattice rotates when an external electric field boldE is applied in such a way that the magnetic planes and the vector of the electric polarization remain always orthogonal.…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the typical values of U eff chosen for Fe d orbitals in BFO lie between 3 and 5 eV [25,27,53,54,28,55,15,56,16], the accuracy of calculated unit cell parameters and P s depends more on the choice to use the PBE+U method at all, rather than on the particular value of U eff one chooses. Thus, within the range of U eff usually considered in the context of BFO, we conclude that the crystal structure varies negligibly with U eff .…”
Section: Polarisationmentioning
confidence: 99%
“…Эти модели были основаны на аналогичных моделях и подходах, которые были разработаны и использовались в предыдущих работах [43][44][45]. Модели были симметризированы для получения более точных систем в процессе оптимизации.…”
Section: результаты и обсужденияunclassified